The impact of public expenditure on the unemployment rate in Algeria: An empirical study using the ARDL Model during the period (1990–2023) - Lagoune, Salim; Bakouche, Lamia; Sahnoune, Farouk; Mansouri, Saadane (The International tax journal, 2025)
This study aims to analyze the impact of public expenditure on the unemployment rate in Algeria during the period (1990–2023), using the Autoregressive Distributed Lag (ARDL) model and annual time series data. The research seeks to estimate the relationship between public spending and unemployment in both the short and long run. The results revealed an inverse relationship between the two variables, indicating that an increase in public spending contributes to reducing the unemployment rate, especially when directed toward productive sectors. Furthermore, the results of the cointegration test showed the existence of a long-term equilibrium relationship between public spending and unemployment. The error correction term (CointEq(-1)) was statistically significant at the 5% level, with an adjustment speed of approximately 40.61%. This implies that the Algerian economy requires about two years and five months to return to equilibrium following any economic shock affecting one of the variables.